Pelatihan Pembuatan Sabun Cuci Piring Dari Bahan Ramah Lingkungan Untuk Meningkatkan Kreativitas Ibu Pkk Desa Janti - Emi Lilawati; Moch Umar Zam Asy'ari; Lailatul Fitria; Ika Khikmatul Latifah; Luklu'ul Maknun (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2023)
Janti Village is one of the villages in Mojoagung subdistrict with a population of around 3,570 people. The Janti village community has a variety of potential, especially in the agricultural and crafts sectors. Janti Village has an obstacle, namely the lack of education to the community regarding regional productivity to produce new products that can be developed into products of high quality and high selling value. Apart from that, people also do not grasp business opportunities and only work according to their abilities, such as working on rice fields and gardens. Method used The implementation method used in this service is a design or framework used to provide information or community mapping (social mapping) directly. This allows for fluid interaction between the community and activity implementers. The results of the service training in making dish soap to increase the creativity of PKK women in Janti Village, can be concluded with the development of entrepreneurship with dish soap products which are used as provisions for PKK women in Janti Village, Mojoagung subdistrict, Jombang regency by directly transmitting the making of dish soap. alternately and how to operate it from the process of ordering the raw materials for dishwashing soap to the homogeneous process that will be packaged. The process of making dishwashing soap really helps PKK women in providing new innovations regarding products that have high economic value Keywords: Soap, Dishwashing, Environmentally Friendly.